Incidence and Factors Predicting Skin Burns at the Site of Indifferent Electrode during Radiofrequency Catheter Ablation of Cardiac Arrhythmias - Hussain Ibrahim; Bohuslav Finta; Jubran Rind (Cardiology Research and Practice)
Radiofrequency catheter ablation (RFA) has become a mainstay for treatment of cardiac arrhythmias. Skin burns at the site of an indifferent electrode patch have been a rare, serious, and likely an underreported complication of RFA. The purpose of this study was to determine the incidence of skin burns in cardiac RFA procedures performed at one institution. Also, we wanted to determine the factors predicting skin burns after cardiac RFA procedures at the indifferent electrode skin pad site. Methods. A retrospective case control study was performed to compare the characteristics in patients who developed skin burns in a 2-year period. Results. Incidence of significant skin burns after RFA was 0.28% (6/2167). Four of the six patients were female and all were Caucasians. Four controls for every case were age and sex matched. Burn patients had significantly higher BMI, procedure time, and postprocedure pain, relative to control subjects (p < 0.05, one-tailed testing). No one in either group had evidence of dispersive pad malattachment. Conclusions. Our results indicate that burn patients had higher BMI and longer procedure times compared to control subjects. These findings warrant further larger studies on this topic.